Using choice experiments to assess smallholder farmers' preferences for pig breeding traits in different production systems in North-West Vietnam. Analysis - Roessler, R.; Drucker, Adam G.; Scarpa, R.; Markemann, A.; Lemke, U.; Thuy, T.Le; Zárate, Anne Valle (2008)
Livestock form key components of the livelihood strategies of many of the world's poorest people. However, despite the potential to alleviate poverty and improve food security through livestock development interventions, the lack of smallholders' participation in the planning and design of breeding programs has often been a major cause of the failure of such programs. Particularly in developing countries where livestock production is still mostly subsistence-oriented and livestock fulfil manifold functions a considerable number of livestock breeding programs have failed. The development of adequate tools to characterise these functions, bearing in mind that these are expressed only rarely in properly functioning markets, is therefore important. This paper seeks to advance the application of such methodologies to the smallholder pig sector in Vietnam. A choice experiment was applied across 140 households involved in pig breeding in order to assess farmers' preferences and the trade-offs for a list of adaptive and productive traits. These included growth, reproduction, disease resistance, feed requirements and appearance. The findings indicate that smallholders highly value both adaptive and performance traits, particularly in resource-driven (i.e. subsistence) production systems. Performance traits were more highly valued in the demand-driven (i.e. market-oriented) systems. These findings have implications for breeding program breed choice and breeding objectives.